Utility of fat‐free adipose tissue correction formula for tracking body composition changes with dual‐energy X‐ray absorptiometry - Moore, Sam R.; Baker, Paul A.; Smith‐Ryan, Abbie E. (Clinical physiology and functional imaging, 2025)
Introduction Fat loss is often the target of weight loss interventions; however, preservation of lean soft tissue (LST) may be more important for health and weight maintenance. Though some LST loss may be inevitable when tracking body composition changes using dual‐energy X‐ray absorptiometry (DXA), correcting for the fat‐free component of adipose tissue (FFAT) in DXA‐derived LST (DXALST) has been proposed. This analysis sought to evaluate differences between DXALST and FFAT‐corrected LST (FFATLST) amongst varied populations and interventions to understand application of the correction formula on LST outcomes. Methods 226 subjects were analyzed across five prior studies. Three studies evaluated combined nutrition and exercise (high‐intensity interval training [HIIT] or high‐intensity resistance training [HIRT]) interventions, including HIIT + HIRT with pre‐ and post‐nutrient timing (HIITRT), HIIT + essential amino acids (HIITAA), and HIRT + protein (HIRTPRO). Remaining studies evaluated HIIT (HIITOW) and protein following bariatric surgery (BARPRO). Pre and post total body DXA scans were used to measure DXALST, body mass, and fat mass (FM). The correction formula was applied to calculate FFATLST. Paired sample t‐tests were used to evaluate differences between DXALST and FFATLST change scores (Δ) across all subjects, within each study and intervention. Results Significant differences between ΔDXALST and ΔFFATLST were observed for BARPRO (mean difference [MD; ΔDXALST–ΔFFATLST] ± standard error [SE]: −3.5 ± 1.2 kg, p < 0.001), as well as HIRTPRO (−0.1 ± 0.2 kg, p = 0.004). Discussion When evaluating LST, the FFAT correction may be specifically applicable to cases of significant weight loss (>10% of original weight) or body recomposition (≥2% FM loss and ≥2% LST gain).